1994
DOI: 10.1002/art.1780371112
|View full text |Cite
|
Sign up to set email alerts
|

Increased usage of vβ2 and vβ6 in rheumatoid synovial fluid t cells

Abstract: Objective. To determine if the T cell antigen receptor V, usage of unstimulated rheumatoid arthritis (RA) synovial fluid (SF) T cells is biased compared with those in peripheral blood (PB).Methods. Freshly isolated, matched synovial fluid and peripheral blood T cells were analyzed for V, gene expression using quantitative polymerase chain reaction (PCR) methods. Ten synovial fluid samples from the knees of 7 patients with RA were studied. The PCR assay used 26 V , primers with a constant region C, primer, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 42 publications
(11 reference statements)
4
17
0
Order By: Relevance
“…Another observation that does not support random clonal expansion is that not all genes analyzed were found to be used by the expanded clonotypes, particularly BV5S1, as also noted by others (5,19), which is normally highly expressed and might account for 5-20% of total TCRBV expression (8,15,33). Moreover, the repeated observation of T cell clones expressing members of particular TCRBV gene families, such as BV1, BV2, BV3, BV6, BV8, and BV12, could be connected to the increased expression of several of these genes identified previously in the synovia of RA patients (2,(5)(6)(7). Clearly, functional in vitro studies with T cell clones and synovial antigens or synthetic peptide libraries will be required to characterize the specificity of the clonotypes expanded in the inflamed joints and to determine the nature of the stimulus.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Another observation that does not support random clonal expansion is that not all genes analyzed were found to be used by the expanded clonotypes, particularly BV5S1, as also noted by others (5,19), which is normally highly expressed and might account for 5-20% of total TCRBV expression (8,15,33). Moreover, the repeated observation of T cell clones expressing members of particular TCRBV gene families, such as BV1, BV2, BV3, BV6, BV8, and BV12, could be connected to the increased expression of several of these genes identified previously in the synovia of RA patients (2,(5)(6)(7). Clearly, functional in vitro studies with T cell clones and synovial antigens or synthetic peptide libraries will be required to characterize the specificity of the clonotypes expanded in the inflamed joints and to determine the nature of the stimulus.…”
Section: Discussionmentioning
confidence: 51%
“…Several lines of evidence, including the massive T cell infiltration in inflamed joints and the association with particular MHC class II molecules, clearly implicate autoreactive T cells in the pathogenesis of this disease (1). Previous studies on TCR usage by synovial T cells, although sometimes conflicting, often indicated clonal expansions, either documented by TCR cloning and sequencing or suspected on the basis of altered V gene expression profiles (2)(3)(4)(5)(6)(7). Generally, however, polyclonal T cell repertoires were observed, probably due to large cell populations secondarily attracted to the affected joints by inflammatory factors.…”
Section: Introductionmentioning
confidence: 99%
“…T cell receptor ␤-chain usage in her blood mononuclear cells was measured by a quantitative polymerase chain reaction (10) and the degree of heterogeneity of the T cell repertoire was assessed by amplification of T cells of the BV 22JB1s6 subfamily. The PCR product was cloned using a TOPO TA cloning kit (Invitrogen, Carlsbad, CA 92008), and colonies were selected randomly and sequenced.…”
Section: Methodsmentioning
confidence: 99%
“…The DNAwas mixed with specific amplification primers and the amplified DNAwas electrophoresed in 3 % agarose gels stained with ethidium bromide to control amplification before hybridization. Details have been described elsewhere [18]. Nylon membranes (Schleider and Schuell, Keene, N. H., USA) were prepared as described [18], prehybridized for 30 min and then hybridized for 1 h at 53°C.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…Details have been described elsewhere [18]. Nylon membranes (Schleider and Schuell, Keene, N. H., USA) were prepared as described [18], prehybridized for 30 min and then hybridized for 1 h at 53°C. Stringency washing was performed at 55°C for 15 min and the DIG-labelled (digoxigenin-AP) PCR products were detected by alkaline phosphatase (Boehringer Mannheim, Mannheim, Germany).…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%